Adaptation, validation and reliability testing of sensory processing measure home form Malay version for children with autism - Noor Mukminin Ahmad; Masne Kadar; Chai, Siaw Chui; Hanif Farhan Mohd Rasdi; Nor Afifi Razaob@Razab; Dzalani Harun (Penerbit Universiti Kebangsaan Malaysia, 2020)
Inappropriate responses towards sensory input received from the environment, also known as sensory processing difficulties (SPD) may affect daily living activities of the children with Autism Spectrum Disorder (ASD). Sensory Processing Measure Home Form (SPM Home Form) as a parent report measure for SPD is available in English and other foreign languages. To enhance the applicability and meaningfulness of SPM Home Form for the Malay speaking population, a study that focuses on translating, adapting, and validating the SPM Home Form into the Malay language was conducted. The development of the Malay version of the SPM Home Form (SPM-MV Home Form) involved three steps: 1) Item evaluation, 2) Forward and backward translation, and 3) Expert review and content validity. The process of translation and adaptation of the form was performed according to standard guidelines. No item was excluded from the original SPM Home Form as all the items were considered by the expert panel as appropriate and relevance to evaluate the activity and social participation among children in Malaysia. Content validity as measured by 10 experts in occupational therapy is high. The mean of sub-scales I-CVI is between 0.96 and 1.00. The total S-CVI of the form is 0.95 with sub-scales S-CVI range between 0.82 and 1.00. Cronbach’s alpha for internal consistency was reported at 0.80 and ICC for test-retest reliability ranged from 0.80 to 0.97. The SPM-MV Home Form has high potential to be used for assessing SPD among children ages 5-12 years in Malaysia.